Energy and spectral efficiency of leakage-based precoding for large-scale MU-MIMO systems - Tran, Tuong Xuan (2016)
We study the capacity performance of signal-toleakage- and-noise ratio precoding scheme (SLNR-PS) for largescale multiuser multiple-inputmultiple-output systems.We derive capacity bounds of SLNR-PS when the number of base station antennas N is large. A trade-off between energy efficiency (EE) and spectral efficiency (SE) is defined for the case of equal power allocation. Based on this trade-off, the closed-form expressions of optimal SE and optimal number of BS antennas for maximizing EE are derived, respectively. In addition, we consider the EE optimization problem under both maximum transmit power and quality of service constraints. The energy-efficient power allocation scheme is obtained to solve this optimization problem. Numerical simulations verify the benefits of the proposed scheme.